Cabo Verde - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Cabo Verde’s risk of external and overall debt distress is rated “high” as in the previous debt sustainability analysis (DSA). The present value (PV) of public and publicly-guaranteed (PPG) external debt-to-GDP ratio breaches its threshold in 2019-2022 under the baseline and protractedly under stress test scenarios. The PV of total public debt-to-GDP ratio is projected to recede below its threshold from 2026 under the baseline and breaches its prescribed limit under stress test scenarios. The debt sustainability assessment is predicated on sustained fiscal consolidation and successful restructuring of state-owned enterprises (SOEs). Prudent borrowing policies and a strengthened debt management strategy are critical to containing debt accumulation. In view of Cabo Verde’s vulnerability to exogenous shocks, growth-enhancing structural reforms remain critical to bringing public debt to sustainable levels.